Pricing Strategies and Customer Satisfaction in Coffee Shops: A Case Study in Camarines Norte, Philippines - Mabeza, Ma. Reina A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study examines the impact of pricing strategies on customer sat-isfaction, aiming to improve customer experiences and foster long term loyalty within the coffee shops business in Camarines Norte, Philippines for the year 2022. Utilizing a descriptive correlational research design, data was collected through face-to-face interviews with 150 respondents selected via purposive sampling. The findings reveal that the majority of respondents were females aged 15-30, vis-ited coffee shops weekly. Sixty-two (62) percent of the respondents describe that coffee shops establishments used competitive-based pricing. Among various pricing strategies, value-based pricing was perceived as the most effective, with an average rating of 4.60. Re-spondents strongly agreed that service quality aligned with pricing strategies significantly influences customer satisfaction, scoring an average of 4.26. A test of significant relationship using Biserial corre-lation coefficient between competitive pricing, value-based pricing, and product bundle pricing regarding the impact on customer satis-faction cues indicate a statistically significant relationship at p<0.05, denoting a positive relationship between the pricing strategies and customer satisfaction. The study concludes that pricing strategies is a crucial element of the marketing mix that directly affects customer satisfaction and business profitability. Although, no universal pricing strategy may exist, understanding customer satisfaction is essential for identifying effective pricing policies. Therefore, it is recommended that coffee shops need to develop comprehensive business models to enhance pricing strategies aimed at increasing market share and sus-taining growth in the coffee shop sector.